Effects of estradiol benzoate on the ultrastructure of the pinealocyte in the ovariectomized rat - Kus, I; Oner, H; Ozogul, C; Ayar, A; Ozen, OA; Sarsilmaz, M; Kelestimur, H (Maghira & Maas Publications, 2002)
OBJECTIVE: The aim of this study was to examine the effects of ovariectomy and ovariectomy followed by estradiol benzoate administration on the ultrastructure of pinealocytes in female rat. DESIGN: For this purpose 15 female Wistar rats were used. Animals were divided into three groups. Group I and II were designated as sham-ovariectomized (control) and ovariectomized, respectively. Group III was ovariectomized and daily injected with estradiol benzoate for one month. At the end of the experiment, all animals were anesthetized with ketamine for fixation by vascular perfusion. Pineal glands of groups I, II and III were removed. All specimens were examined by electron microscopy. RESULTS: Ovariectomy caused an increase of lipid droplets, mitochondria and ribosomes. Rough endoplasmic reticulum was extensive in the cytoplasm. Estradiol administration to ovariectomized rats resulted in formation of less extensive lipid droplets, mitochondria and ribosomes compared to pinealocyte ultrastructure of both control and ovariectomized rats. Extensiveness of rough endoplasmic reticulum in the pinealocytes of estradiol-administrated rats was similar to that in controls. CONCLUSIONS: The results confirm relationship between the pineal gland and gonads in the rat and it has been suggested that estradiol benzoate reverses the ultrastructural changes, which indicate increased cell activation, occurring in the pinealocytes after ovariectomy.
Keywords: pinealocyte; ultrastructure; ovariectomy; estradiol; rat